2014
DOI: 10.1097/iop.0b013e31828956a8
|View full text |Cite
|
Sign up to set email alerts
|

Orbital B-Lymphocyte Depletion in a Treatment Failure of Rituximab for Thyroid Eye Disease

Abstract: Rituximab is an emerging treatment for thyroid eye disease. Rituximab effectively depletes circulating CD20+ B-lymphocytes; however, its effect on target tissues has not been well-studied. Failures of rituximab have been infrequently reported. The authors describe a patient treated with rituximab for thyroid eye disease who failed to respond to treatment, and underwent orbital decompression. Orbital fat samples and peripheral blood samples were evaluated for the presence of CD20+ B-lymphocytes. Complete deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…One case report has demonstrated B-cell depletion from the blood and orbital fat of a TED patient treated with rituximab who still went on to require orbital decompression for worsening disease [18]. A separate, prospective, randomized, double-blinded, placebo-controlled trial compared treatment with two rituximab infusions versus two saline infusions, given 2 weeks apart, in 21 patients with TED.…”
Section: Key Pointsmentioning
confidence: 95%
“…One case report has demonstrated B-cell depletion from the blood and orbital fat of a TED patient treated with rituximab who still went on to require orbital decompression for worsening disease [18]. A separate, prospective, randomized, double-blinded, placebo-controlled trial compared treatment with two rituximab infusions versus two saline infusions, given 2 weeks apart, in 21 patients with TED.…”
Section: Key Pointsmentioning
confidence: 95%
“…Failure of RTX was reported in one patient whose GO progressed to acute DON (21) and in one who already had DON (22) and failed to improve on RTX despite achieving peripheral B cell depletion. On the other hand, another ten patients with DON reviewed in the paper by Salvi et al (6) have responded to RTX with improvement of their visual sight.…”
Section: Rituximab In Go: Pretrial Experiencementioning
confidence: 99%
“…Rituximab induces cell apoptosis by binding to the CD20 membrane antigen in both normal and malignant B cells (12). In addition, it significantly depletes lymphocytes not only in the blood but also in the target tissue, and the effect remained significant 2 months after rituximab infusion (13). Based on the pharmacological mechanism of rituximab, clinical trials on autoimmune diseases have indicated the potential use of rituximab as a candidate treatment for autoimmune diseases (14).…”
Section: Discussionmentioning
confidence: 99%